Reconstruction of Medial Wall Blowout Fracture Defect with a Combination of Resorbable Meshed Plate and Cancellous Bone Allograft. (15th October 2019) - Shin, Jongweon; Park, Song I; Hwang, Yunsup; Kwon, Ho; Shim, Hyung-Sup
Abstract : Background. Various materials are available for the reconstruction of bone defects in cases of medial wall blowout fracture. This study was conducted to assess the efficacy of the combination of a resorbable meshed plate and cancellous bone allograft. Methods. From March 2014 to March 2017, a total of 111 patients were evaluated. Sixty-three patients received reconstruction surgery with porous polyethylene plates (control group) and the other forty-eight patients underwent operation with a resorbable meshed plate plus allogenic cancellous bone (combined group). The results were assessed by exophthalmometric measurements, width, and volume discrepancies as compared with the unaffected orbit, and operation time. Results. The difference in exophthalmometric measurements between the affected and unaffected orbits were 0.94 ± 0.70 mm in the control group and 1.05 ± 0.73 mm in the combined group without statistical significance (p = 0.425 ). In the analysis of computed tomography images, the width discrepancy was 1.55 ± 0.86 mm and 1.08 ± 0.69 mm, respectively (p = 0.003 ); however, the volume discrepancy demonstrated no statistically significant difference (2.58 ± 1.40 cm 3 versus 2.20 ± 1.80 cm 3 ;p = 0.209 ). Operation time was significantly shorter in the combined group as compared with the control group (43.0 ± 7.0 versus 38.3 ± 7.0 minutes;p = 0.001 ). Conclusion. The combination material composed of resorbable meshed plate and cancellous bone allograft made reconstruction surgery of medial wall blowout fracture easier and quicker to perform with long-lasting results.